Mass spectrometry-based stable-isotope tracing uncovers metabolic alterations in pyruvate kinase-deficient Aedes aegypti mosquitoes. (June 2020) - Petchampai, Natthida; Isoe, Jun; Horvath, Thomas D.; Dagan, Shai; Tan, Lin; Lorenzi, Philip L.; Hawke, David H.; Scaraffia, Patricia Y.
Abstract: A recent in vitro characterization of a recombinant pyruvate kinase (PK) from Aedes aegypti mosquitoes demonstrated that the enzyme is uniquely regulated by multiple allosteric effectors. Here, we further explored PK gene and protein expression, and enzymatic activity in key metabolic tissues of mosquitoes maintained under different nutritional conditions. We also studied the metabolic effects of PK depletion using several techniques including RNA interference and mass spectrometry-based stable-isotope tracing. Transcriptional analysis showed a dynamic post-feeding PK mRNA expression pattern within and across mosquito tissues, whereas corresponding protein levels remained stable throughout the time course analyzed. Nevertheless, PK activity significantly differed in the fat body of sucrose-, blood-fed, and starved mosquitoes. Genetic silencing of PK did not alter survival in blood-fed females maintained on sucrose. However, an enhanced survivorship was observed in PK-deficient females maintained under different nutritional regimens. Our results indicate that mosquitoes overcame PK deficiency by up-regulating the expression of genes encoding NADP-malic enzyme-1, phosphoenolpyruvate carboxykinase-1, phosphoglycerate dehydrogenase and glutamate dehydrogenase, and by decreasing glucose oxidation and metabolic pathways associated with ammonia detoxification. Taken together, our data demonstrate that PK confers to A. aegypti a metabolic plasticity to tightly regulate both carbon and nitrogen metabolism. Graphical abstract: Image 1 Highlights: Pyruvate kinase (PK) activity in fat body varies in response to nutritional changes. PK silencing enhances survival in females maintained under specific nutritional regimens. PK-deficient females increase transcript levels of specific genes. PK knockdown reduces the abundance of metabolites involved in several pathways.